2014
DOI: 10.1021/jp500427t
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Ionic Cells: Two Solutions to Store Solar Energy and Generate Electricity on Demand

Abstract: Inward flux {-kb*STh_o + kf*STh, 0} Flux type General inward flux Used products COMSOL Multiphysics 1.4.5 Inflow 1 Equations Settings Settings Description Value Concentration {0, 0} Apply reaction terms on All physics (symmetric) Use weak constraints 0 Used products COMSOL Multiphysics 1.4.6 Outflow 1 Equations Used products COMSOL Multiphysics 1.5 General Form PDE 2 (Light) Settings Description Value Shape function type Lagrange Settings Name Value Handling of sharp corners Trimming Boundary Layer Properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…Attention has been paid to the compatibility between photobatteries and textiles to fabricate wearable photobatteries. [121][122][123] Photobatteries are not limited to the lithium-ion batteries; [124] the charging of lithium-air batteries, [125,126] zinc-air batteries, [127] lithium-sulfur batteries, [128] silver-zinc batteries, [77] fuel cells, [129] and flow batteries [85,[130][131][132][133][134][135][136][137][138][139][140] facilitated by the light illumination are also available. However, the solar energy conversion efficiencies in these energy storage materials are relatively low, which hinder their further deployment in photobatteries.…”
Section: Examples Of Photobattery Materialsmentioning
confidence: 99%
“…Attention has been paid to the compatibility between photobatteries and textiles to fabricate wearable photobatteries. [121][122][123] Photobatteries are not limited to the lithium-ion batteries; [124] the charging of lithium-air batteries, [125,126] zinc-air batteries, [127] lithium-sulfur batteries, [128] silver-zinc batteries, [77] fuel cells, [129] and flow batteries [85,[130][131][132][133][134][135][136][137][138][139][140] facilitated by the light illumination are also available. However, the solar energy conversion efficiencies in these energy storage materials are relatively low, which hinder their further deployment in photobatteries.…”
Section: Examples Of Photobattery Materialsmentioning
confidence: 99%
“…[ 700,701 ] Extra-and intra-structural device integration, as discussed above, is easier to realize yet, presents some intrinsic drawbacks. [ 694,702,703 ] The potential of constructing one of the two devices on top of the other, has been recently demonstrated by painting a LIB on top of prefabricated solar cells.…”
Section: Hybrid Devicesmentioning
confidence: 99%
“…Direct integration, and hybridization of solar cells with or within energy storage cells (batteries, supercapacitors and other) has attracted great attention recently . Extra‐ and intra‐structural device integration, as discussed above, is easier to realize yet, presents some intrinsic drawbacks .…”
Section: Unconventional Techniques and Configurationsmentioning
confidence: 99%
“…In recent years, the integration of batteries and solar cells into the same enclosure, as well as the development of shared electrode designs between batteries and solar cells, are being investigated . For example, Paolella et al reported a two‐electrode system using N719 dye as a mixed photocathode and directly photo‐oxidizing LiFePO 4 nanocrystals with light irradiation .…”
Section: Introductionmentioning
confidence: 99%